Lexical variation in the Whatsapp application in Spanish students speaking of secondary education - Castillo Reyes, Analí Corina (2023)
In the virtual world in which we are immersed, we find a diversity of virtual groups that create their own simplified language to facilitate communication among themselves. This simplified language is found in the virtual groups formed by high school students. This paper aims to identify the types of simplification most used in this application by high school students. The present paper aims to identify the types of simplification most used in this application by high school students. The research is qualitative. The corpus of the research is based on two virtual groups, Experiment and Neighborhood, in which 52 conversations were collected. The study concludes that there are three types of simplification of linguistic units and the most predominant is the elision of vowels within words. The variationist approach will be applied to explain and interpret the data.